2020
DOI: 10.1103/physrevlett.125.121105
|View full text |Cite
|
Sign up to set email alerts
|

Spurious Point Source Signals in the Galactic Center Excess

Abstract: We reexamine evidence that the Galactic Center Excess (GCE) originates primarily from point sources (PSs). We show that in our region of interest, non-Poissonian template fitting evidence for GCE PSs is an artifact of unmodeled north-south asymmetry of the GCE. This asymmetry is strongly favored by the fit (although it is unclear if this is physical), and when it is allowed, the preference for PSs becomes insignificant. We reproduce this behavior in simulations, including detailed properties of the spurious PS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(123 citation statements)
references
References 23 publications
8
115
0
Order By: Relevance
“…Because the spatial morphology of the GC excess cannot be reliably derived from the data (as discussed at length in this review; see Section 2.2 in particular), spatial templates to model it are judiciously chosen. Recent investigations of the GC excess with the NPTF technique have revealed that if the GC excess is not spatially symmetric (as is generally assumed) and the asymmetry is not properly modeled, then the results of the NPTF technique are not reliable (98,99). Preliminary evidence also indicates that the GC excess might indeed present a north-south asymmetry (above and below the Galactic plane) and be smooth (rather than point-like) (98,99).…”
Section: Non-poissonian Photon Statistics Templatementioning
confidence: 99%
“…Because the spatial morphology of the GC excess cannot be reliably derived from the data (as discussed at length in this review; see Section 2.2 in particular), spatial templates to model it are judiciously chosen. Recent investigations of the GC excess with the NPTF technique have revealed that if the GC excess is not spatially symmetric (as is generally assumed) and the asymmetry is not properly modeled, then the results of the NPTF technique are not reliable (98,99). Preliminary evidence also indicates that the GC excess might indeed present a north-south asymmetry (above and below the Galactic plane) and be smooth (rather than point-like) (98,99).…”
Section: Non-poissonian Photon Statistics Templatementioning
confidence: 99%
“…Moreover, it does not present any spurious effect at the Fermi-LAT threshold (∼ 10 −10 ph cm −2 s −1 ), and IPS are resolved down to ∼ 10 −11 ph cm −2 s −1 for | | > 0.5 • , depending on the modeling of the smooth GCE component. This holds true even when no GCE smooth template is included neither in the skyFACT fit nor in the 1pPDF one, contrary to what happens using non-optimized diffuse models [10,12]. We therefore demonstrate, also in the context of 1pPDF methods, that reducing large-scale residuals from mis-modeling of the diffuse emission improves the reconstruction of PS / .…”
Section: Pos(icrc2021)677mentioning
confidence: 70%
“…The limitations of such a systematic uncertainty are indeed also relevant for the reconstruction of faint PS with 1pPDF methods. On the other hand, the skyFACT optimization procedure mitigates possible systematics related to the mis-modeling of unaccounted components [10], by allowing spatial re-modulation in the fit templates. Besides the bulge, we also consider NFW126 as smooth GCE in the 1pPDF analysis (1pPDF-NFW126).…”
Section: Pos(icrc2021)677mentioning
confidence: 99%
See 1 more Smart Citation
“…While promising, it has also been suggested that the GCE signal could be generated by millisecond pulsars [16,17]. In recent years, the debate surrounding the origin of the GCE has intensified [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. New measurements in the coming decade and a better theoretical understanding of Galactic diffuse emission models will help settle this debate, but until then, the origin of the GCE remains unknown and dark matter annihilation remains a viable explanation.…”
Section: Jhep03(2021)123mentioning
confidence: 99%